(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Chikitsamanjari is a traditional book widely used in Kerala after Ashtanga Hrudaya. Kerala Ayurveda physicians use this book as a quick reference for day to day clinical practice. Even though different types of Swedana procedures are elaborated in Brihathrayis, this book explains several types of Swedas using the drugs that are widely available and that can be done easily. The text has explained simple and effective internal and external treatments for Vataja diseases. The description of various single drug remedies in the local language is another noticeable feature of this clinical treatise. Dhara with milk, Pottali Sweda with Chincha leaves (Tamarindus indica) and coconut scraping are some examples. Some of the unique contributions of Chikitsamanjari include, preparation of Dhanyamla, the procedure of Avagaha Sweda, its duration and Samyak Lakshanas, usage of different medicinal herbs for preparation of Potali Sweda in various disease conditions and Dhara using Tila Taila, milk and different combinations. Management of Pittadhika Vata with Dhara is one of the contributions of Chikitsamanjari. This paper reviews application of various Swedakriyas in Chikitsamanjari with respect to Vatavyadhi.